Politics of modern muslim subjectivities : islam, youth, and social activism in the middle east - Jung, Dietrich; Petersen, Marie Juul.; Sparre, Sara Lei.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Examining modern Muslim identity constructions, the authors introduce a novel analytical framework to Islamic Studies, drawing on theories of successive modernities, sociology of religion, and poststructuralist approaches to modern subjectivity, as well as the results of extensive fieldwork in the Middle East, particularly Egypt and Jordan.
Keywords: Science; Science, general